2000
DOI: 10.1016/s0168-6496(00)00078-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of humic substances-degrading bacterial isolates from an estuarine environment

Abstract: Bacterial isolates were obtained from enrichment cultures containing humic substances extracted from estuarine water using an XAD-8 resin. Eighteen isolates were chosen for phylogenetic and physiological characterization based on numerical importance in serial dilutions of the enrichment culture and unique colony morphology. Partial sequences of the 16S rRNA genes indicated that six of the isolates were associated with the K subclass of Proteobacteria, three with the Q-Proteobacteria, and nine with the Gram-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…These organisms include members of the roseobacter group (3), Agrobacterium species (5,30,32), Acinetobacter species (11,31,42), and Bacillus species (23). 3,4-PCD activity has not been found in members of the rhodobacter group or the Halomonadaceae group (in which isolates SE37 and SE96 cluster), although both of these groups contain members capable of metabolizing aromatic compounds (9,35).…”
Section: Resultsmentioning
confidence: 99%
“…These organisms include members of the roseobacter group (3), Agrobacterium species (5,30,32), Acinetobacter species (11,31,42), and Bacillus species (23). 3,4-PCD activity has not been found in members of the rhodobacter group or the Halomonadaceae group (in which isolates SE37 and SE96 cluster), although both of these groups contain members capable of metabolizing aromatic compounds (9,35).…”
Section: Resultsmentioning
confidence: 99%
“…At present we can only speculate about the ecological role of Actinobacteria in different types of freshwaters. Members of this lineage might be able to utilize refractory humic substances, as is known for other gram-positive Bacteria, including actinobacterial genera (13,20). Humic substances are a prominent component of the dissolved organic carbon pool in many systems (6, 24) (e.g., in Lake Fuchskuhle) and an important carbon source for aquatic Bacteria (2,34).…”
Section: Abundant Freshwater Bacteria With Gram-positive Cell Walls?mentioning
confidence: 99%
“…Studies on bacterial isolates capable of utilizing humic substances have shown these bacteria to be phylogenetically and physiologically diverse. Aerobic isolates include α‐ and γ‐ Proteobacteria and Gram‐positive bacteria (Esham et al ., 2000) and anaerobic isolates include Proteobacteria of all subdivisions as well as Acidobacteria (Coates et al . 2002).…”
Section: Introductionmentioning
confidence: 99%